Reexpansion Pulmonary Edema following Tube Thoracostomy in a Pediatric Patient with Anterior Mediastinal Mass. (19th May 2022) - Choi, Sung-Wook; Romeo, Deborah A.; Gutman, David A.; Smith, Jennifer V.
Abstract : Reexpansion pulmonary edema (RPE) is an exceedingly rare and potentially fatal complication of a rapidly reexpanded lung following evacuation of air or fluid from the pleural space secondary to conditions such as a mediastinal mass, pleural effusion, or pneumothorax. Clinical presentations can range from mild radiographic changes to acute respiratory failure and hemodynamic instability. The rapidly progressive nature of the disease makes it important for clinicians to appropriately diagnose and manage patients who develop RPE. We present a case of a child with a large malignant pleural effusion who developed severe RPE after tube thoracostomy and ultimately required venoarterial extracorporeal membrane oxygenation (VA-ECMO). The patient was 7-year-old Caucasian male with newly diagnosed ambiguous T cell myeloid leukemia. A chest computerized tomography (CT) demonstrated a large pleural effusion causing tracheal shift and left bronchus compression as well as an anterior mediastinal mass causing compression of the right atria and right ventricle. Tube thoracostomy was performed in the operating room (OR) with deep sedation. The procedure was complicated with hypoxemia, bradycardia, and pulseless cardiac arrest. After return of spontaneous circulation, the child continued to have refractory hypoxemia, profound hypotension, and frothy secretions. Endotracheal intubation was performed with a size 5.0 cuffed endotracheal tube. Chest radiograph demonstrated opacification of the left hemithorax with chest infiltrates. Patient required VA-ECMO for circulatory support. Supportive therapy of RPE was continued and decannulation was done on day three. Tracheal extubation was performed on day five.